Sustainable Development and Fostering Inclusive Growth Through Microfinance in the Indian Economy - P. S., Anuradha; Ganesan, G. (Indian Journal of Finance, 2010)
The Indian story of growth, especially in the post liberalization era, has been overshadowed by multiple human development issues. Exclusion has been identified as the primary reason for unequal distribution of the benefits of growth. The emergence of inclusive growth in the policy paradigm is the outcome. The purpose of this paper is to focus on social & economic issues and the use of microfinance as a strategy for inclusive growth & sustainable development.India has vast diversity in the areas of language, religion, culture and social norms. Since the inception of India as an independent country, population explosion has been projected as a prime concern of the state. Soon after independence, Indian leaders were thinking of strategies of economic development the country should follow. The top priority of the Indian Government was to have rapid growth in a stagnant economy. India decided to follow a socialistic pattern of society, which meant growth with social justice, self-reliance and poverty alleviation. Stress was laid on rapid industrialization and for shift from its historic agrarian-based economy to a mixed economy with sectoral balance. The fall-out was creation of heavy industries and a larger role of the public sector. In the process, the Government neglected rural economy and rural population, which is almost 2/3rd of the total population. In 1991,the Government of India introduced economic reforms. Globalization, industrialization, liberalization and privatization led to tremendous economic growth. This growth carried the characteristic feature of urban centric saturation. The prevalent disparities in the form of social, spatial and regional disparities were aggravated due to this unplanned approach. An attempt has been made in this paper to look at sustainable development & inclusive growth as the most pragmatic approach for addressing the multiple development disparities.